THE INFLUENCE OF LEADERSHIP STYLE AND WORK FACILITIES ON PERFORMANCE EMPLOYEES THROUGH COMMUNITY SATISFACTION: PENGARUH GAYA KEPEMIMPINA DAN FASILITAS KERJA TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN MASYARAKAT - Ndruru, Marina (UPMI Proceeding Series, 2024)
Problem How big is the influence of leadership style, work facilities on employee performance through community satisfaction as an intervening variable in the Patumbak District Head Office? The research method for obtaining empirical data was carried out using an explanatory survey method. The data collection technique uses a closed questionnaire using a Likert scale model and interviews. The population and research sample were 48 employees of the sub-district office of Patumbak District. Data analysis is the Product Moment Correlation Coefficient with the t-test statistical test. The research results are based on a large correlation test. The influence of leadership style on employee performance is 0.754 where the critical table r product moment (n = 20) with df = 95% has a t table number = 0.423 where rxy = 0.754 > 0.423. This states that Leadership Style has a significant influence on Employee Performance at the Subdistrict Office of Patumbak District. The Influence of Work Facilities is 0.800 where the critical table r product moment (n = 20) with df = 95% there is a t table number = 0.423 where rxy = 0.800 > 0.423 The results of this study suggest that the better the Leadership Style and the work facilities that employees have, this will be followed by better employee performance at the Patumbak District Head's office. The magnitude of the influence of leadership style on employee performance through the variable Job Satisfaction as an Intervening variable is 0.805 where the critical table r product moment (n = 20) with df = 95% has the number t table = 0.423 where rxy = 0.805 > 0.423, The results of this research suggest that the better the Leadership Style and work facilities that employees have, the better the Employee Performance will be in the Patumbak District Head's office. The magnitude of the influence of leadership style on employee performance through the variable Job Satisfaction as an Intervening variable is 0.805 where the critical table r product moment (n = 20) with df = 95% there is a t table = 0.423 where rxy = 0.805 > 0.423 based on the results of these findings concepts and theories Leadership Style, Work Facilities, Community Satisfaction developed in this research, the variables Leadership Style and Work Facilities through job satisfaction displayed at the Patumbak District Head Office are good. In relation to the management, the issue of Leadership Style, Work Facilities and Community Satisfaction can be guided and developed to support the